Pharmacogenetics of chronic pain and its treatment - Světlík, Svatopluk; Hronová, Karolína; Bakhouche, Hana; Matoušková, Olga; Slanař, Ondřej (Mediators of inflammation, 2013)
This paper reviews the impact of genetic variability of drug metabolizing enzymes, transporters, receptors, and pathways involved in chronic pain perception on the efficacy and safety of analgesics and other drugs used for chronic pain treatment. Several candidate genes have been identified in the literature, while there is usually only limited clinical evidence substantiating for the penetration of the testing for these candidate biomarkers into the clinical practice. Further, the pain-perception regulation and modulation are still not fully understood, and thus more complex knowledge of genetic and epigenetic background for analgesia will be needed prior to the clinical use of the candidate genetic biomarkers.
Keywords: cytokiny; farmakogenetika; Humans; Biomarkers; Cytokines; Chronic Pain; biologické markery; Pharmacogenetics; lidé; chronická bolest